Azienda Ospedaliera Universitaria Meyer. Attività sanitaria e scientifica 2011 - Majer, Katalin; Sirianni, Luigi (Proceedings e report, 2013)
The Meyer University Hospital Report on health and scientific activity is a valuable tool for sharing and disseminating information that summarises the working methods, the results and the lines of improvement that must be particularly committed. It is an instrument of knowledge and evaluation which is therefore intended for a use both inside and outside the hospital. A dynamic tool, which must be perfected, together with the improvements pursued by the hospital.